Hindu Nationalist in India - "Malik, Yogendra K." (New Delhi, 1994)
Table of Contents Ideology, Power, and Political Parties The Bharatiya Janata Party: Its Heritage and Leadership Strategies: Collaboration, Alliances, Cooperation, and Confrontation Policies and Issue Orientations Organization, Decision-Making, and Supportive Groups Electoral Performances: National and State Levels Conclusion: Summary, Assessments, and Prospects Bibliography Index
Keywords: Bharatiya Janata Party-India